Programmed environmental illumination during autologous stem cell transplantation hospitalization for the treatment of multiple myeloma reduces severity of depression: A preliminary randomized controlled trial. (11th August 2018) - Valdimarsdottir, Heiðdís B.; Figueiro, Mariana G.; Holden, William; Lutgendorf, Susan; Wu, Lisa M.; Ancoli‐Israel, Sonia; Chen, Jason; Hoffman‐Peterson, Ariella; Granski, Julia; Prescott, Nina; Vega, Alejandro; Stern, Natalie; et al.
Abstract: Background: Over a third of multiple myeloma (MM) patients report clinical levels of depression during autologous stem cell transplant (ASCT) hospitalization. We report preliminary results from a randomized clinical trial investigating the effect of Programmed Environmental Illumination (PEI) of hospital rooms on depression. Methods: Patients (N = 187) scheduled to receive an ASCT were assessed for eligibility. Those who met study eligibility criteria (n = 44) were randomly assigned to one of two PEI conditions involving delivery of either circadian active bright white light (BWL) or circadian inactive dim white light (DWL) throughout the room from 7 to 10 am daily during hospitalization. Patients completed the Center for Epidemiological Studies Depression Scale (CES‐D) prior to hospitalization, at days 2 and 7 post‐transplant, and on the third day of engraftment. Results: General linear model analyses revealed no difference between the groups in CES‐D total score at baseline ( P  =   0.7859). A longitudinal linear mixed model analysis revealed a significant interaction between time of assessment and light condition [ F (3, 107) = 2.90; P  =   0.0386; ɳ 2  = 0.08)], indicating that PEI prevented the development of depression during hospitalization, with effects reaching significance by the third day of engraftment. At the third day of engraftment, 68.4% of the participants in the DWL comparison condition met the criteria for clinically significant depression compared to 42.1% in the BWL condition. Conclusion: These findings demonstrate that PEI using BWL during MM ASCT hospitalization is effective in reducing the development of depression. Future studies should examine the mechanisms whereby PEI improves depression. Abstract : Over a third of Multiple Myeloma patients report clinical levels of depression during autologous stem cell transplant hospitalization. In this manuscript, it was found that Programmed Environmental Illumination of the hospital room using Bright White Light was effective in reducing the development of depression.